Delivery Order (DO) Online Implementation In Accelerating Document Flow Service Of Imported Goods In Payment Companies. (July 2020) - Sultra, R.A.P.J.; Nabela, R. M. C.; Wibisono, G; Sirait, D. P.
Abstract: Delivery Order (DO) Online is a delivery order redeemer from shipping lines by the freight forwarders electronically. It is an electronic order delivery service to speed up the service of imported goods expenditure from a port so that the flow of documents and the flow of goods is efficient. The purpose of this research is to explain Delivery Order Online and the obstacles of Delivery Order Online in Shipping Companies. The research method used was qualitative descriptive research. Sources of data in this study were primary data by conducting interviews with related parties and secondary data by data collection from the research site. The results of the study showed that the implementation of DO Online has a positive impact on service users, that is, it can speed up the flow of documents and the flow of imported goods in the ports and have some obstacles in shipping companies.